Design, synthesis, and biological evaluation of novel fluorinated pyrazole encompassing pyridyl 1,3,4-oxadiazole motifs - Desai, Nisheeth C.; Kotadiya, Ghanshyam M.; Trivedi, Amit R.; Khedkar, Vijay M.; Jha, Prakash C. (Medicinal Chemistry Research, 2016)
A rational approach was adopted for the synthesis of 1-(2-(3-(4-fluorophenyl)-1-phenyl-1H-pyrazol-4-yl)-5-(pyridin-4-yl)-1,3,4-oxadiazol-3(2H)-yl)-3-(aryl)prop-2-en-1-ones (5a-n) using conventional heating as well as microwave irradiation techniques. Compounds 5a-n were tested for their in vitro antimicrobial activity and cytotoxicity. Compounds 5g showed most potent antibacterial activity, while compound 5k emerged as the most effective antifungal agent. The most active compounds 5f, 5g, 5l, and 5m were also screened against methicillin-resistant Staphylococcus aureus. Among these compounds, 5g and 5m inhibited the growth against MRSA at low level of cytotoxicity. A binary quantitative structure-activity relationship based recursive partitioning model was developed to probe the physico-chemical properties influencing the structure-activity relationship for this class of molecules, which was used to correctly classify active and inactive compounds.

Conventional and microwave-assisted organic synthesis of novel antimycobacterial agents bearing furan and pyridine hybrids - Desai, Nisheeth C.; Bhatt, Kandarp; Jadeja, Dharmpalsinh J.; Mehta, Harsh K.; Khedkar, Vijay M.; Sarkar, Dhiman (Drug Development Research, 2022)
Drug resistance in tuberculosis poses a serious threat to humanity because currently available antitubercular drugs are ineffective against Mycobacterium tuberculosis (M. tuberculosis). As a result, the approval of Bedaquiline and Delamanid for the treatment of drug-resistant tuberculosis was accelerated. Still, there is an urgent need to search for new antitubercular drugs with novel mechanisms of action (MoA). Due to this, we have designed a synthetic strategy by utilizing microwave-assisted organic synthesis. We have compared our method with the conventional procedure, and the data show that our procedure is more effective in the preparation of title compounds. A unique series of 1-(2-(furan-2-yl)-5-(pyridin-4-yl)-1,3,4-oxadiazol-3(2H)-yl)-3-(aryl)-pr op-2-en-1-ones (5a-o) was synthesized utilizing conventional and microwave-assisted techniques. Synthetic compounds were investigated for antitubercular activity against Mycobacterium TB H37Ra and Mycobacterium bovis (M. bovis). Compound 5b was reported to be the most effective against M. tuberculosis H37Ra (97.69 percent inhibition at 30 mu g/ml) and M. bovis (97.09 percent inhibition at 30 mu g/ml). An in silico binding affinity study of mycobacterial enoyl-acyl carrier protein reductase (InhA) reveals the binding mechanism and thermodynamic interactions that determine these molecule's binding affinity. Compound 5b had a high glide score of -8.991 and low glide energy of -49.893 kcal/mol.
Keywords: Antitubercular activity; microwave-assisted organic synthesis; Molecular docking